Pancytopenia caused by allopurinol and azathioprine interaction in a heart transplant patient: a case report. Issue 6 (15th November 2020) - Feinman, Jason; Rollins, Brett; Contreras, Johanna; Parikh, Aditya
Abstract: Background: Azathioprine is an immunosuppressive now less commonly prescribed after orthotopic heart transplantation. Patients with solid organ transplantation are at increased risk for numerous comorbidities including gout. Co-administration of allopurinol for gout prophylaxis and azathioprine increases the risk for severe myelosuppression due to drug–drug interactions. Case summary: A 57-year-old male with a history of heart transplant 6 years prior presented with a month of severe fatigue and shortness of breath. His admission laboratory values were notable for severe pancytopenia. Medical workup revealed no haematologic malignancy, viral infection, or other consumptive process. After extensive review, it was discovered that the patient was taking excessive allopurinol for gout. His haematologic abnormalities resolved following discontinuation of allopurinol and treatment with filgrastim and romiplostim and was able to be discharged from the hospital. Discussion: Azathioprine and allopurinol can potentially cause profound cytopenias due to the increased production of the active metabolites of azathioprine. Given the association between gout and solid organ transplantation, recognition of the risks of medication interaction as well as communication amongst health care providers and between providers and their patients is paramount.